The difficulties of the professional woman : then and now. - Teo, Cassandra Kim Choo. (2012)
Drawing on Jane Barker's The Galesia Trilogy and Elizabeth Gilbert's Eat Pray Love, my paper will analyze the difficulties shared by the professional women in the eighteenth and twenty-first century, at the same time commending the efforts and the strength in character of both women authors in striving to overcome the conventional expectations of women. However, while they share some historical stigmas, I assert that there is evidence of progress in the representation of the 21st century professional woman, in terms of her increased agency within her relationship with men and in being recognized as a professionally productive woman.The longstanding trappings of the eighteenth century conventional female are, as illustrated in Eat, Pray, Love, not much different from the expectations that women face today. However, in resolving the difficulties that the eighteenth century conventional female face, the twenty-first century professional woman is able to escape conventional expectations and achieve her aims. This essay essentially showcases the difficulties of being a professional woman and recognizes her efforts in attempting to break free from social conventions. My thesis finally acknowledges the progress that the twenty-first century professional woman has made in her increased agency within her relationship with men and also in being recognized and accepted by society as a professionally productive woman.